The prospects for stormwater harvesting in Cape Town, South Africa using the Zeekoe Catchment as a case study - Okedi, John (Department of Civil Engineering, 2019)
The City of Cape Town in South Africa faced the possibility of taps running dry in 2018 because of a prolonged drought that commenced in 2015. With such droughts expected to reoccur frequently in future, this study investigated the prospect for stormwater harvesting (SWH) and use as an alternative water resource - selecting the 89 km2 Zeekoe Catchment situated on the southern part of Cape Town as a case study. The study assessed potential to supply partially treated stormwater to non-potable water needs or fully treated water to potable water demands. The study determined that there was temporal mismatch between the identified non-potable water demands and the stormwater that is seasonally available from winter rainfall. Due to the mismatch, balancing storage was required in the range of 20 - 30% of the mean annual stormwater volume estimated at 18 Mm3 . The 61 stormwater ponds in the Zeekoe Catchment were assessed to determine the capacity to provide the required storage. Since the stormwater ponds were mainly for flood-control, the opportunity for multi-use was investigated using RealTime-Control (RTC). RTC would allow for extended storage in the stormwater ponds for water supply and pre-emptive draining before storm events for flood control. The application of RTC on the stormwater ponds provided a capacity of 1 Mm3 (about 5.5% of the mean annual stormwater volume). The capacity was inadequate as the stormwater supplied from the storage would only meet 44 - 60% of the demands, with a spill (water lost as overflow) of 35 - 51%. To provide additional capacity, an assessment was undertaken in stepwise increments of 1 Mm3 to determine the optimal storage required from the shallow lakes (vleis) in the study area i.e. Zeekoevlei and Rondevlei. It was determined that after 4 Mm3 , there was limited increase in demand met and reduction in spill. Stormwater could also be abstracted, fully treated to potable water standards and injected into the local potable water distribution system. Alternatively, the abstracted water from the vleis could be pre-treated at a new proposed WTP in the study area and then pumped to one of the existing water treatment plants. The assessment to determine influence of storage on quantity of stormwater supplied as discussed for non-potable water was undertaken for potable water. It was determined that for potable water that is required all the year round, the supply was not sensitive to changes in storage volume. Since the influence of balancing storage was limited, optimisation of SWH system was based on plant capacity to maximise supply and minimise spillage. The available surface water storage i.e. stormwater ponds and vleis are currently used for other purposes such as flood control, recreation - including sailing - and to maintain ecology that require a permanent pool of water. The sensitivity of these activities was the driver for the study to consider alternative storage options such as groundwater aquifers. The study area had an unconfined aquifer with sandy soils that could support Managed Aquifer Recharge. The physical characteristics in the Zeekoe Catchment, i.e. largely flat terrain, pervious sandy soils and a relatively deep unconfined aquifer (20 - 50 m) would support typical borehole abstraction rates of 3.5 - 8.1 L/s per borehole from some 140 boreholes. This would provide a mean annual groundwater yield of 29 - 33 Mm3 (about 15% of Cape Town water demand in 2018). Overall, stormwater harvesting from groundwater storage was more advantageous than surface water as it provided larger water quantities and improved water quality. This study has contributed towards identification of an alternative water resource by considering the possibilities of SWH from surface and groundwater storage for supply to potable and non-potable demands at a catchment scale. The study determined that the optimal use of stormwater requires a shift in the use to potable water uses. Treatment to potable standards would also eliminate the potential public health risks from cross connections. It was also determined that the treatment to potable water standards is more cost-effective for SWH at a catchment scale (centralised system) than using the water for non-potable purposes as it eliminates the need for the costly dual reticulation. Accordingly, this study recommends SWH and reuse to be for potable water needs where the abstraction is from a single location and the distribution through the existing potable water system. The factors that were determined to be important for the efficacious application of SWH included inter alia the availability of storage (surface or groundwater), the catchment characteristics (terrain, soil types, level of development, population density), and seasonal availability of the stormwater resource (winter or all year rainfall). The study also assessed the impact of land use and climate changes on the quantity of the stormwater. In terms of wider application, the study has provided insight into opportunities for stormwater use with partial or full treatment for non-potable or potable water demands respectively. The study has also provided a useful understanding of the potential scale and magnitude of the available non-potable water needs. It was also noted that reliability of the SWH was a function of storage capacity especially for supply to non-potable demands and the local rainfall regime. These issues need to be assessed to determine the prospects and viability of SWH and reuse in the given area.